The linkages between water supply, sanitation and hygiene and small-scale irrigation: Insights from rural Ethiopia - Bryan, Elizabeth; van Biljon, Chloé; Lee, Yeyoung; Ringler, Claudia; Mekonnen, Dawit Kelemework (IWA Publishing, 2025)
While small-scale irrigation is largely designed and developed for agricultural production, irrigation water is used for multiple other purposes in rural low- and middle-income settings where dedicated water, sanitation, and hygiene services (WASH) are not available. Therefore, expanding access to irrigation can potentially improve the WASH environment leading to health and nutrition benefits. This study examines the linkages between irrigation, use of irrigation water sources for multiple purposes, and WASH and health outcomes. We find that irrigation is associated with better household access to water and improved sanitation facilities. This relationship is driven by households that use groundwater for both irrigation and domestic uses. Moreover, our results show that hygiene practices and health outcomes are not influenced by irrigation or multiple uses of the same water source. To strengthen hygiene behavior, behavioral change communication will be important. For small-scale irrigation to effectively support WASH and, thus, to strengthen nutrition and health outcomes, systems would need to be co-designed by irrigation and health specialists, and women farmers who are largely responsible for providing WASH services at the household level would need to be empowered to participate in the design and management of these dual-purpose systems.